2004
DOI: 10.1111/j.0962-1075.2004.00508.x
|View full text |Cite
|
Sign up to set email alerts
|

A functional analysis of ACP‐20, an adult‐specific cuticular protein gene from the beetle Tenebrio: role of an intronic sequence in transcriptional activation during the late metamorphic period

Abstract: A gene encoding the adult cuticular protein ACP-20 was isolated in Tenebrio. It consists of three exons interspersed by two introns, intron 1 interrupting the signal peptide. To understand the regulatory mechanisms of ACP-20 expression, ACP-20 promoter-luciferase reporter gene constructs were transfected into cultured pharate adult wing epidermis. Transfection assays needed the presence of 20-hydroxyecdysone, confirming that ACP-20 is up-regulated by ecdysteroids. Analysis of 5' deletion constructs revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 91 publications
2
14
0
1
Order By: Relevance
“…The result implied the existence of ecdysone-responsive region between À387-to þ26-bp of BMWCP10. A similar observation was reported by Lemoine et al (2004), who observed the highest promoter activity of the adult cuticular protein gene, the ACP-20 5 0 -flanking region in the presence of 10 mM 20E.…”
Section: Discussionsupporting
confidence: 87%
“…The result implied the existence of ecdysone-responsive region between À387-to þ26-bp of BMWCP10. A similar observation was reported by Lemoine et al (2004), who observed the highest promoter activity of the adult cuticular protein gene, the ACP-20 5 0 -flanking region in the presence of 10 mM 20E.…”
Section: Discussionsupporting
confidence: 87%
“…This intron is located after the fourth codon, a position that is very common for cuticle genes in various insect species, and may reflect a conserved and important function for cuticle gene expression (Binger and Willis, 1994;Lemoine et al, 2004). To date, the importance of this intron has been demonstrated only for the Tenebrio ACP20 gene, using tissue cultures (Lemoine et al, 2004). In Drosophila, robust expression levels of the EDG84 and EDG78 cuticle genes do not require the presence of the first intron (Kawasaki et al, 2002;Murata et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The Tenebrio ACP22 gene encodes a protein that accumulates in the exocuticle layers, but not in the epicuticle (Bouhin et al, 1992a;Lemoine et al, 1989), yet it is stimulated within 3 h by injection of exogenous 20E (Bouhin et al, 1993). As noted above, the ACP20 gene of Tenebrio, also, does not seem to exhibit a typical response to a 20E pulse (Braquart et al, 1996;Lemoine et al, 2004). Taken together, these observations warrant further studies of 20E regulation of genes for exocuticle proteins, as they could possibly hint at novel mechanisms at work early during cuticle synthesis, and acting maybe in parallel with the well demonstrated "pulse" type of regulation.…”
Section: Cp Genes Not Regulated By a Pulse Of 20ementioning
confidence: 95%
“…Many CP genes possess an intron that interrupts the signal peptide coding sequence, which suggests a function in gene expression (Binger and Willis, 1994;Charles et al, 1997;Lemoine et al, 2004). In addition, among the 88 Drosophila proteins having a "phase 0" intron localized after the fourth codon, a striking proportion (43%) are annotated as cuticle proteins (Nielsen and Wernersson, 2006).…”
Section: Role Of Intronic Sequencesmentioning
confidence: 99%